2019
DOI: 10.7324/japs.2019.91111
|View full text |Cite
|
Sign up to set email alerts
|

Ceratobasidium ramicola IBRLCM127, an endophytic fungus isolated from Curcuma mangga Valeton & Zijp with strong anti-candidal activity

Abstract: Ceratobasidium ramicola IBRLCM127, an endophytic fungus isolated from the rhizome of the local medicinal plant Curcuma mangga Valeton & Zijp, was found to possess significant anti-candidal activity. This fungal endophyte was cultivated in submerged fermentation system using yeast sucrose medium supplemented with host plant water extract and cultivated at 25°C, agitated at 120 rpm for 12 days. The ethyl acetate was used as a solvent to extract compounds in the fermentative broth. The fungal ethyl acetate extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…A previous study reported that bactericidal/fungicidal drugs are clinically more powerful antibiotic agents compared to bacteriostatic/ fungistatic drugs since this type of drug can kill bacteria and rather effective in severely immunocompromised patients. 3 The present findings also revealed that the endophytic fungus, Muscodor sp. secrete more bioactive compounds extracellularly into the fermentative broth compared to intracellular.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A previous study reported that bactericidal/fungicidal drugs are clinically more powerful antibiotic agents compared to bacteriostatic/ fungistatic drugs since this type of drug can kill bacteria and rather effective in severely immunocompromised patients. 3 The present findings also revealed that the endophytic fungus, Muscodor sp. secrete more bioactive compounds extracellularly into the fermentative broth compared to intracellular.…”
Section: Discussionsupporting
confidence: 72%
“…Disc diffusion assay for test bacteria was performed according to the procedures described by Taufiq & Darah 1 . Meanwhile, for test fungi, the methods described by Mu'azzam & Darah 3 was employed. Chloramphenicol (30 µg/ml) and Ketoconazole (30 µg/ml) were used as positive controls for bacteria and yeast/fungi, respectively whereas 1.0 % of DMSO was set as a negative control.…”
Section: Disc Diffusion Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…This endophyte had potential anti-candidal activity. The fungal ethyl acetate extract showed significant inhibitory zones against C. albicans (MIC = 2.5 mg/ml [ 82 ]. C. longa showed the presence of forty-four endophytic.…”
Section: Role Of Genus Curcuma Members In Agingmentioning
confidence: 99%